Analysis of Students’ Literacy and Numeracy Skills in the Implementation of the Minimum Competency Assessment (Phase D) in Junior High Schools - Hasanah, Uswatun; Nur, Hasah; Mukhlisin, Mukhlisin; Taha, Syamsumarlin; Syafar, A. Muhammad (International journal of technology and education research, 2025)
This study aims to analyze the literacy and numeracy ability of students in the implementation of the Minimum Competency Assessment (AKM) in Phase-D in Pinrang Regency. AKM is part of the National Assessment program which aims to measure the minimum competence of students in the aspects of literacy, reading and numeracy. The research data was taken from the results of the National Assessment report card at seven junior high schools in Pinrang Regency. The method used in this study is quantitative descriptive, with data analyzed based on the categories of AKM outcomes, namely: Need for Special Intervention, Basic, Capable, and Advanced. The results of the study showed that the literacy skills of students were mostly in the Basic and Proficient categories, while for numeracy, the majority of students were still in the Basic category. This indicates that most students have basic skills in understanding reading texts and solving numeracy problems, but still need strengthening, especially in critical and reflective thinking skills on texts and contextual problems. Factors that affect the results of this AKM include the availability of learning resources, teacher competence, student learning motivation, and support for the school and family environment. The results of this study are expected to be evaluation materials for schools, local governments, and related parties in designing strategies to improve students' literacy and numeracy skills, especially in Pinrang Regency.This research aims to analyze students' literacy and numeracy abilities in the implementation of the Minimum Competency Assessment (AKM) in Phase-D in Pinrang Regency. AKM is part of the National Assessment program which aims to measure the minimum competence of students in the aspects of literacy, reading and numeracy. The research data was taken from the results of the National Assessment report card at seven junior high schools in Pinrang Regency.